Determinasi Input Sensorik dan Latihan Keseimbangan Terhadap Risiko Jatuh Lansia: Tinjauan Pustaka Sistematis - Zulfah, Khairina; Komalasari, Dwi Rosella; Pristianto, Arif; Jatmiko, Safari Wahyu (JUKEJ : Jurnal Kesehatan Jompa, 2025)
In recent decades, the global elderly population has increased. As a person ages, the risk of progressive balance disorders increases, increasing the risk of falls. 30% of elderly people in Indonesia will experience falls by 2022. This increasingly requires treatment for fall risks in the elderly to improve their quality of life in old age. Currently, there is a lot of research on improving the balance of the elderly. However, there is still no further research related to the combination of floor surfaces with decreasing sensory input in the elderly, so that more sensory input is needed in the elderly. This study aims to identify the effect of floor surfaces and sensory input on balance and fall risk in the elderly. This research method uses a literature review using four main databases: PubMed, SAGE, Medline, and ScienceDirect. The journals used were published in 2020-2025. The data obtained were then analyzed using Prism Diagrams, and the journal search obtained 3,914 journals before screening. After reviewing, 5 journals were obtained and then analyzed using the PICO technique. Results: A review of five journals found that sensory input-based interventions and floor surface variations were effective in improving balance and reducing the risk of falls in older adults. Conclusion: Sensory input-based interventions and floor surface variations were effective in improving balance and reducing the risk of falls in older adults.